2022
DOI: 10.3390/cancers14225721
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis-Related Molecular Subtypes and Immune Features Associated with Hepatocellular Carcinoma

Abstract: Bioinformatics tools were used to identify prognosis-related molecular subtypes and biomarkers of hepatocellular carcinoma (HCC). Differential expression analysis of four datasets identified 3330 overlapping differentially expressed genes (DEGs) in the same direction in all four datasets. Those genes were involved in the cell cycle, FOXO signaling pathway, as well as complement and coagulation cascades. Based on non-negative matrix decomposition, two molecular subtypes of HCC with different prognoses were iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…These studies have performed differential gene analysis on liver cancer data from multiple datasets of the TCGA database and GEO. These studies have identified GNA14 as one of the key characteristic genes that affect the prognosis of liver cancer patients (Yu et al 2020a ; Ye et al 2022 ). Subsequent experiments have confirmed the discovery that GNA14 is a prognostic protective gene in patients with liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have performed differential gene analysis on liver cancer data from multiple datasets of the TCGA database and GEO. These studies have identified GNA14 as one of the key characteristic genes that affect the prognosis of liver cancer patients (Yu et al 2020a ; Ye et al 2022 ). Subsequent experiments have confirmed the discovery that GNA14 is a prognostic protective gene in patients with liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified several genes functioning in cell adhesion. GNA14, encoding a member of the guanine nucleotide binding, or G protein family, was a wellknown target in hepatocellular carcinoma and vascular tumors (85,86). The protein encoded by NLGN4Y (Neuroligin 4 Y-Linked) is presented at the postsynaptic side of the synapse (87).…”
Section: Genome-wide Crispr-cas9 Screening Of Arsenic Trioxide In Hap...mentioning
confidence: 99%